Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3390/md8051518
|View full text |Cite
|
Sign up to set email alerts
|

Chitin and Chitosan as Multipurpose Natural Polymers for Groundwater Arsenic Removal and As2O3 Delivery in Tumor Therapy

Abstract: Chitin and chitosan are natural polysaccharide polymers. These polymers have been used in several agricultural, food protection and nutraceutical applications. Moreover, chitin and chitosan have been also used in biomedical and biotechnological applications as drug delivery systems or in pharmaceutical formulations. So far, there are only few studies dealing with arsenic (As) removal from groundwater using chitin or chitosan and no evidence of the use of these natural polymers for arsenic trioxide (As2O3) deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Analysis of the possible interactions between chitin and zirconia nanoparticles with Raman spectroscopy confirmed that formation of chitin-ZrO2 hybrid materials is due to hydrogen bond formation between chitin and ZrO2 [137,160]. These chitin-zirconia composites are increasingly attractive for various applications, such as the construction of advanced zirconia-based hydrogen peroxide biosensors [192], adsorbents of heavy metals [193,194] and materials for biomedical devices [195][196][197].…”
Section: Extreme Biomimetics: Development Of Chitin-based Inorganic-omentioning
confidence: 93%
“…Analysis of the possible interactions between chitin and zirconia nanoparticles with Raman spectroscopy confirmed that formation of chitin-ZrO2 hybrid materials is due to hydrogen bond formation between chitin and ZrO2 [137,160]. These chitin-zirconia composites are increasingly attractive for various applications, such as the construction of advanced zirconia-based hydrogen peroxide biosensors [192], adsorbents of heavy metals [193,194] and materials for biomedical devices [195][196][197].…”
Section: Extreme Biomimetics: Development Of Chitin-based Inorganic-omentioning
confidence: 93%
“…As a result, the protonation of amine groups on chitosan with lower pH pzc values is more easier to adsorb, which leads to the continuous release of hydroxide ions to the aqueous medium (-NH 2 + H + ⇔ -NH 3 + ) (Kwok et al 2014). Amine protonation and zeta potential will increase with the decrease of the pH at the surface of the chitosan (Kwok et al 2009(Kwok et al , 2014Sacco and Masotti 2010;Gerentea et al 2010). In most cases, the lower pH that may be 5.5 and lowest can get better results.…”
Section: Ph Effectmentioning
confidence: 97%
“…It plays an important role in the performance. Because they have different density, porosity, specific surface area, and its surface charge in terms of the point of zero charge (Kwok et al 2009;Sacco and Masotti 2010;Hanh et al 2015;Gerentea et al 2010), thus it does deep effect on the sorption. Small particles can relatively cause the large specific surface area, and it will increase the sorption of the chitosan.…”
Section: Shape Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, research has focused on the study of chitinous products and their derivatives and, in particular, chitosan, which is the most economically attractive [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%